Synthesis of Copper Oxide Nanostructures by Ar Plasma Jet and Study of Their Structural and Optical Properties - Abbas, Bahaa Hassoun; Abdalameer, Nisreen Kh; Mohammed, Raghad S. (Iraqi Journal of Science, 2024)
This paper used argon plasma jets to prepare CuO nanostructures. Several techniques, including UV–Vis spectroscopy, X-ray diffraction (XRD), X-ray energy dispersive spectroscopy (EDS), and scanning electron microscopy (SEM), were used for the characterization of the prepared CuO nanoparticles. UV–Vis spectroscopy analysis confirmed that the CuO nanostructures have an energy band gap of 2.7 eV. The XRD analysis showed that the CuO nanostructures have an average crystallite size of 36 nm. Furthermore, the results of the EDX examination demonstrated the creation of CuO nanostructures of high purity. The scanning electron microscope was used to analyze the surface morphology, showing a high agglomeration rate. According to SEM analysis, the average diameter of CuO nanoparticles was 10 nm.